Novel Polyurethanes Based on Recycled Polyethylene Terephthalate: Synthesis, Characterization, and Formulation of Binders for Environmentally Responsible Rocket Propellants - Florin Marian Dîrloman (MDPI AG, 2021)
Novel polyurethane-based binders, specifically designed for environmentally responsible rocket propellant composites, were obtained by employing the polyester-polyols that resulted from the degradation of polyethylene terephthalate waste. A new class of “greener” rocket propellants, comprising polyurethanes (based on recycled PET) as the binder, phase stabilized ammonium nitrate (PSAN) as the eco-friendly oxidizer, and triethylene glycol dinitrate (TEGDN) as the energetic plasticizer, together with aluminum as fuel and Fe2O3 as the catalyst, is herein reported. The components of the energetic mixtures were investigated (individually and as composite materials) through specific analytical tools: 1H-NMR, FT-IR, SEM-EDX, DTA and TGA, tensile and compression tests, DMA, and micro-CT. Moreover, the feasibility of this innovative solution is sustained by the ballistic performances exhibited by these composite materials in a subscale rocket motor, proving that these new formulations are suitable for rocket propellant applications.